Tindak Tutur Direktif dan Ekspresif pada Naskah Drama “Ayahku Pulang” Karya Usmar Ismail (Perspektif : Jurnal Pendidikan dan Ilmu Bahasa, 2026)
The research conducted this time aims to analyze both directive and expressive speech acts in the drama script 'Ayahku Pulang' by Usmar Ismail. The background factor of this research is to investigate the relationship between the dialogues of the characters in the drama script and the concepts of directive speech acts and expressive speech acts in the process of social interaction. The purpose of this research is to significantly contribute to the field of pragmatics and speech acts, to find out the frequency of the existence of directive and expressive speech acts in the drama script, and to provide references and new data analysis in pragmatics. The research was conducted by referring to a qualitative descriptive approach and a theoretical approach using a pragmatic approach. The data collection process was conducted using the listening and note-taking methods, and subsequent data analysis employed the distribution method. Based on the analysis carried out, data were obtained for 28 directive speech acts and 31 expressive speech acts, which will then be classified in more detail according to their types. It is hoped that this research will be beneficial both from a scientific and societal perspective, enriching the literature on pragmatic studies, helping to improve public understanding of speech acts, and raising awareness of the importance of analyzing drama scripts as a representation of everyday social interactions in society.